Antibiotic and non-antibiotic treatment of urinary tract infections in the era of growing antimicrobial resistance - Sara Wawrysiuk; Małgorzata Żebrowska (Kazimierz Wielki University, 2020)
Urinary tract infection is one of the most common indications for prescribing antibiotics among otherwise healthy patients. The lifetime risk of having urinary tract infection among the female population reaches up to 50%. Empirical antibiotic therapy is the first line of treatment in uncomplicated cases. Bacterial resistant to antibiotics is constantly increasing and it is resulting in the evolvement of multidrug-resistant pathogens but also causes a limitation in empirical treatment options. Due to growing antimicrobial resistance, local antimicrobial susceptibility patterns should always be considered especially when empirical treatment is introduced. The article shows the ongoing need for updates in local resistance patterns. Recommendations for the empirical treatment should be constantly verified with reference to the local antimicrobial resistance status. Non-antibiotic preparations may be useful only in the prevention of urinary tract infections.